Analisis Pengaruh Cash Flow untuk Memprediksi Kondisi Financial Distress Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Ni Putu Oka Marheni; Anak Agung Ayu Erna Trisna Dewi; I Wayan Kartana (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2022)
The title of this study is cash flow influence analysis to predict financial distress conditions in companies listed on the Indonesia Stock Exchange. The formulation of the problem in this study is whether total cash flow, operating cash flow, investment cash flow, and funding cash flow affect Financial Distress in manufacturing companies on the Indonesia Stock Exchange. The purpose of this research is to prove empirically the influence of total cash flow, operating cash flow, investment cash flow and cash flow funding on the prediction of financial distress in a company listed on the Indonesia Stock Exchange. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2014-2019. While the sampling technique used in this study is purposive sampling, which is sample determination technique with certain considerations, and can be as many as 17 companies. The data collection method used is the documentation method. Data analysis techniques include classical assumption tests, which consist of normality tests, multicollinearity tests, autocorrelation tests and heteroskedasticity tests, multiple regression analysis. The results showed that (1) total cash flow affects financial distress. (2) Operating cash flow has no effect on financial distress. (3) Investment cash flow affects financial distress. (4) Funding cash flow has no effect on financial distress.